Determination of Dimensions and Items of Outpatient Service Quality for Ahvaz Hospitals - Farzad Faraji Khiavi; Mohammad Qolipour; Zahra Dashtinejad; Iman Mirr (Tehran University of Medical Sciences, 2018)
Background and Aim: Assessing service quality is one of the basic requirements to develop outpatient service. There is no valid and reliable tool to measure quality of outpatient service, therefore this study was performed to determine dimensions and items for assessing service quality of outpatient in Iran. Materials and Methods: To determine dimensions and items of the outpatient service quality, a cross-sectional study was conducted with participating of 550 outpatients referred to Ahvaz hospitals in year 2015. To determine content validity, the Delphi technique (3 rounds) with participating of 8 quality experts was used. Construct validity of the tool was assessed through exploratory and confirmatory factor analysis. Reliability was assessed using Cronbachchr('39')s alpha coefficient. Data were analyzed by Excel, Spss, and Lisrel softwares. Results: The content validity of tool with CVI=0.94 was confirmed. According to exploratory factor analysis, the hospital outpatient service quality tool included 36 items and 11 dimensions (choosing the service provider, communication and interaction, having authority, continuity of service, quality of facilities and basic amenities, respect, immediate and timely attention, safety, prevention, access and reliability). Construct validity of the tool was confirmed based on the goodness of fit quantities of model (RMSEA=0.007, CFI= 0.99, GFI=0.95). Conclusion: The results of study showed that the outpatient SERVQUAL tool with 36 items and 11 dimensions was a valid and reliable tool to measure quality of outpatient service in Iranian hospitals.